2015
DOI: 10.17700/jai.2015.6.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Mobile devices in agriculture: attracting new audiences or serving the tech-savvy?

Abstract: A B S T R A C TThe latest wave of ICT-innovations are based around mobility (smart phones, tablets, wireless networks etc.). Mobility can be a decisive success factor of ICT-adoption, because of the spatial, local and remote nature of farming. New generation mobile devices can also have a lower barrier to entry in terms of skills and cost for the user/farmer. The question is whether these new devices, especially smart phones and tablets are adopted by the farmers who are already using computers and Internet or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The use of ICT can play a key role in agriculture [10] as they allow to improve the production chains, the management and marketing of the production, as well as the management of land and its natural resources [1]. The role of ICT in agriculture can be summarized as follows [11]: "[...] it may be safely stated that modern large scale farming technology [...] controlled by state of the art information and communication technology has the potential for substantial reductions of the production costs for agricultural commodities.…”
Section: Market Informationmentioning
confidence: 99%
“…The use of ICT can play a key role in agriculture [10] as they allow to improve the production chains, the management and marketing of the production, as well as the management of land and its natural resources [1]. The role of ICT in agriculture can be summarized as follows [11]: "[...] it may be safely stated that modern large scale farming technology [...] controlled by state of the art information and communication technology has the potential for substantial reductions of the production costs for agricultural commodities.…”
Section: Market Informationmentioning
confidence: 99%
“…These applications help Mr. Shinpuku in crop surveillance and detecting crop problems like infection. Research by Csótó (2015) showed that 45% of farmers in Hungary use a smartphone, 14% use tablets, and 72% use a desktop or laptop computer for agricultural purposes, just like Mr. Shinpuku. A survey conducted in the United States, reported by Nelson (2019), showed that 49% of farms use computers and around 80% have internet access.…”
Section: Introductionmentioning
confidence: 99%